Video-Assisted Minithoracotomy Diaphragmatic Plication: Respiratory Effects in Adults - Rombolá, Carlos; Crespo, Marta Genovés; López, Pedro Tárraga; Martínez, Antonio Honguero; Atance, Pablo León; Ramírez, Ana Triviño; Montes, José Antonio Rodríguez (The Thoracic and Cardiovascular Surgeon, 2016)
Objectives The objective of this study was to analyze the clinical respiratory and spirometric effects of video-assisted minithoracotomy diaphragmatic plication (VAM-T DP) in the treatment of diaphragmatic eventration.Methods A retrospective longitudinal study of 18 patients who underwent a VAM-T DP in our service between February 2005 and July 2011 was performed. Data of patient characteristics, preoperative clinical variables, and postoperative results (3, 6, and 12 months) were collected for statistical analysis using the software package SPSS 13.0 for Windows (Wilcoxon test, Friedman test, and Z-test).Results The main clinical respiratory and spirometric variables improved significantly and remained stable over 1 year.Conclusions VAM-T DP is a viable and safe procedure that improves the spirometry values and offers stable results during the first year. To our knowledge, the present series is the second largest published report in English relating to this procedure in adults.
Keywords: diaphragmatic surgery; diaphragmatic plication; respiratory paralysis; diaphragmatic eventration